JA:2021-3. Dissemination and Adoption of AgInjuryNews.org: A Publicly Available Collection of Agricultural Injury Media Reports. Issue 3 (2nd July 2020) - Burke, Richard; Pilz, Matthew; Redmond, Emily; Sauer, Megan; Weichelt, Bryan
ABSTRACT: Purpose : Agriculture, Fishing, and Forestry (AFF) is the most dangerous occupation in the United States with 22.8 fatalities per 100, 000 workers and a youth fatality rate of 28.21 per 100, 000 workers as of 2017. As of 2015, the US Bureau of Labor Statistics' (BLS) discontinued its Census of Fatal Occupational Injuries (CFOI), leaving an absence of a nationally representative agricultural injury surveillance system. AgInjuryNews.org aims to fill this gap in AFF injury surveillance through news media reports. In addition to multiple peer-reviewed publications, a 3-week advertising campaign on Facebook.com was undertaken. This project investigates and discusses these methods of implementation, dissemination, and diffusion throughout the agricultural safety and health discipline. Methods : User data were extracted via Google Analytics from January 27, 2015 to October 1, 2019. Advertising campaign effectiveness was determined through Facebook and Twitter integrated analytics. Tweets from October 1, 2018 to October 1, 2019 were coded into themes and categories and analyzed. Retention is defined as the ratio of returning users to total users and is discussed via common behavioral metrics. Results/Findings : The majority of users were from major US metropolitan areas and areas home to large agricultural research centers. High retention was found in users from areas with a high AFF population and the presence of National Institute of Occupational Safety and Health (NIOSH) agriculture centers. Users from universities and professional agriculture safety and health networks stayed on the site longer and had a lower bounce rate than those from social media. Facebook advertising attracted many new visitors but had poor retention and visit duration. Twitter posts with direct referrals and mentions yielded the highest engagement rate, while article links yielded the most impressions. Practical Application : The AgInjuryNews.org database can be useful to AFF professionals, and its continued growth better enables more informed decision-making and research activities. These findings better inform the methods and channels to use when disseminating AFF safety and health information. Results from this project indicate that Facebook and Twitter can be useful platforms for outreach, but strategies that specifically target agricultural safety and health stakeholders still need refinement.